Design and Build Online Attendance System Using NFC Based on IoT - Suhartono Suhartono; Bayu Adhi Prakosa; Ritzkal Ritzkal (Jurnal Mantik, 2021)
This research designs the Hardware Platform: (1) Ardunio Mega 2560 (2) NFC Sensor PN 532 (3) Buzzer (4) LCD i2C (5) Ethernet shield module, and Software: (1)Windows 10 (2)Arduino IDE 1.8 (2)XAMPP 3.2 (3)PHP (4)MySQL (5)Visual Studio Code 1.5 The system is connected to the Internet Network the data stream will be stored into a MySQL-based database in the NCC Lab, student data obtained from reading the NFC reader will be streamed through the Internet network, where the use of the ethernet shield module can integrate attendance equipment on a computer with a local MySQL database. Integration of Hardware and Software components produces an online attendance system for solutions at SLB ABCD Fitria Bogor, hardware, software and online attendance system services have been tested, with the following results: (1) the success of the system feature test, can refer to the black box test attachment (2) efficiency of attendance administration (3) improve the reporting performance of user agencies. This system solution has never been implemented in SLB ABCD Fitria Bogor schools and probably in many other special schools in Indonesia, which have service features and hardware and software systems that are simple, reliable and easy to implement, so that they can be added value for users, for further research can improve responsive websites.